A LITERARY ARTIST NAMED TOLKIEN: STYLISTIC DEVICES AND PSEUDOTRANSLATION IN HIS LEGENDARIUM - Flores, Leonardo (Coletivo Cine-Fórum Journal, 2025)
This article presents an excerpt from a Master’s research project that comparatively analyzes two Brazilian Portuguese translations of The Fellowship of the Ring, by J. R. R. Tolkien. It proposes a reflection aimed at understanding how stylistic choices and elements of literariness can be preserved or transformed in the translation process. The first part of the text focuses on the contextualization of Middle-earth and the author’s biography. The second part discusses the concept of pseudotranslation and its relevance in Tolkien’s writings, highlighting the importance of translation strategies such as domestication and foreignization. The conclusion indicates that the retranslation tends to preserve more features of the original, although different approaches are possible and valid depending on the translator’s objectives. The article also emphasizes and reinforces the linguistic and aesthetic richness of Tolkien’s works, opening space for further studies on style, language, and translation.